Measurement of the B̄ → Dlv̄ Partial width and form factor parameters - Athanas, M; Avery, P; Jones, C; Lohner, M; Prescott, C; Yelton, J; Zheng, J; Brandenburg, G; Briere, R; Ershov, A; Gao, Y; Kim, D; et al. (1997)
We have studied the decay B̄ → Dlv̄, where l = e or μ. From a fit to the differential decay rate dΓ/dw we measure the rate normalization FD(1)|Vcb| and form factor slope ρ̂D2, and, using measured values of τB, find Γ(B̄ → Dlv̄) = (12.0 ± 0.9 ± 2.1) ns-1. The resulting branching fractions are B(B̄0 → D+l-v̄) = (1.87 ± 0.15 ± 0.32)% and B(B- → D0l v̄) = (1.94 ± 0.15 ± 0.34)%. The form factor parameters are in agreement with those measured in B̄ → D*lv̄ decays, as predicted by heavy quark effective theory.